WARRN – a formulation-based risk assessment procedure for Child and Adolescent Mental Health Services (CAMHS): the view of clinicians. Issue 4 (3rd October 2019) - Gray, Nicola S.; Tiller, Jacqui; Snowden, Robert J.
Abstract : Purpose: Wales Applied Risk Research Network (WARRN) is a formulation-based technique for the assessment and management of serious risk (e.g. violence to others, suicide, etc.) for users of mental health services which has been adopted across most Child and Adolescent Mental Health Services (CAMHS) across Wales. The paper aims to discuss this issue. Design/methodology/approach: An online survey was disseminated to National Health Service clinicians in CAMHS to evaluate their perceptions of the use and effectiveness of WARRN. Data from 88 clinicians were analysed with both quantitative and qualitative methods. Findings: Clinicians reported increased clinical skills, increased confidence in their assessment and management of risk and in safety planning, the increased safety of service users and the general public, and a belief that WARRN had saved lives. The qualitative data showed that clinicians thought a common risk evaluation instrument across Wales and different agencies had created a common language and understanding that improved communication. Practical implications: WARRN appears well accepted in CAMHS services with the view that it is having a very positive effect on service user well-being and safety and could be implemented in other services. Originality/value: This is the first report of a formulation-based approach to the management of serious problem behaviours in CAMHS services.